In Vivo Activity of WCK 4282 (High-Dose Cefepime/Tazobactam) against Serine-β-Lactamase-Producing Enterobacterales and Pseudomonas aeruginosa in the Neutropenic Murine Lung Infection Model - Lasko, Maxwell J. (Antimicrob Agents Chemother, 2021)
WCK 4282 (cefepime 2 g-tazobactam 2 g) maximizes systemic exposure of tazobactam and restores cefepime activity against various extended-spectrum β-lactamase (ESBL)- and cephalosporinase-producing strains in vitro. We describe clinical WCK 4282 exposure efficacies against various serine β-lactamase-producing Enterobacterales and Pseudomonas aeruginosa isolates in a murine pneumonia model. Clinical cefepime-resistant isolates (17 Enterobacterales and 2 P. aeruginosa) were utilized. Isolates expressed ESBLs, cephalosporinases, and/or serine carbapenemases (KPC and OXA-48-like). WCK 4282 MICs were 4 to 32 μg/ml. For in vivo experiments, lungs of neutropenic mice were inoculated using standard inoculum (10(7) log(10) CFU/ml). Serine carbapenemase-producing isolates were also assessed using a low inoculum (1:5 dilution). Treatment mice received a human-simulated regimen (HSR) of cefepime, meropenem (control for serine carbapenemase expression with low inoculum experiments), or WCK 4282 human-simulated regimens. Efficacy was assessed as change in log(10) CFU/lungs at 24 h compared with 0-h controls. At standard inoculum, the mean 0-h bacterial burden was 6.65 ± 0.23 log(10) CFU/lungs, and it increased at 24 h by 2.48 ± 0.60 log(10) CFU/lungs among untreated controls. Initial bacterial burdens of lower inocula ranged from 5.81 ± 0.12 to 6.39 ± 0.13 log(10) CFU/lungs. At standard and/or low inocula, cefepime and meropenem provided minimal activity. WCK 4282 produced a >1 log(10) reduction against 9/9 ESBL-/cephalosporinase-producing strains. WCK 4282 provided variable activity among mice infected with standard or lower inocula of OXA-48-like-producers. WCK 4282 exposures provided 0.53 ± 1.07 log(10) CFU/lungs growth against KPC producers at a standard inoculum versus bacteriostasis (−0.15 ± 0.54 change in log(10) CFU/lungs) at a low inoculum. WCK 4282 produced potent in vivo activity against ESBL- and cephalosporinase-producing Enterobacterales and P. aeruginosa isolates and potential activity against OXA-48-like-producing Enterobacterales isolates in a neutropenic pneumonia model.